INITIATING PAULO FREIRE'S PERSPECTIVE ON THE EDUCATIONAL PARADIGM IN THE INDEPENDENT LEARNING CURRICULUM AND ITS RELEVANCE TO ISLAMIC EDUCATION IN MADRASAH - Taufiqurrohman, Ofik; Misbahuddin, Misbahuddin; Wasehudin, Wasehudin (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research explores Paulo Freire's perspective on Islamic education and its relevance to the Islamic curriculum in madrasahs in prioritizing moral and ethical values. This report uses a comprehensive approach to analyze Freire's 1972 book,